KOMUNIKASI LINGKUNGAN BERBASIS EKOFEMINISME DALAM PENGELOLAAN SAMPAH PERKOTAAN - Ardianti, Dhini; Affandi, Nur Ratih Devi; Indry, Cindy Witria (Linimasa : Jurnal Ilmu Komunikasi, 2026)
Waste management remains a critical urban challenge in Indonesia, particularly in Bandung City, where increasing waste generation demands community-based solutions. Women often play a central role in household and community waste practices, yet their contributions are frequently overlooked. This study adopts an ecofeminist perspective, which links women’s roles with environmental sustainability, to examine their strategic position in addressing waste management issues. The research aims to explore the movements and activities of women waste activists in Bandung, analyze the communication strategies they use to raise public awareness, and propose a model of environmental communication grounded in ecofeminism. Employing a qualitative method with an action research approach, the study emphasizes participatory and collaborative processes. Data were collected through observation, literature review, and in-depth interviews with women activists from several Bandung communities, including Mandalajati, Sumur Bandung, Wates, Jamaras, Cibunut, and Antapani Tengah. Informants were selected purposively, and data analysis followed Miles and Huberman’s interactive model, with triangulation ensuring data validity. The findings reveal that women act as key agents in sorting, processing, and recycling waste. Their communication practices are rooted in values of care, sustainability, and collective responsibility, which enable them to build environmental awareness and influence behavioral change in their communities. Communication strategies identified include direct education, the use of community media, environmental campaigns, and role modeling in everyday life. The study concludes with the formulation of an ecofeminist-based environmental communication model, positioning women as pivotal change agents and emphasizing that sustainable waste management requires inclusive communication and active female participation at the local level.